Analisis Smart Pole Berbasis IoT Untuk Mitigasi Kecelakaan Lalu Lintas Di Jalan Raya - Rodji, Achmad Pahrul; Darusman, Darusman; Wicaksono, Anung; Kuswarno, Dwi (INFORMATICS FOR EDUCATORS AND PROFESSIONAL : Journal of Informatics; Vol 10 No 2 (2025): INFORMATICS FOR EDUCATORS AND PROFESSIONAL : JOURNAL OF INFORMATICS (Desember 2025)DO - 10.51211/itbi.v10i2.3561, 2025)
The highway transportation industry faces significant challenges in managing road safety, especially related to monitoring dynamic environmental and traffic conditions. Systems relying on manual inspection or limited surveillance often fail to respond quickly to dangerous situations. This research aims to address these challenges by developing and analyzing the implementation of an IoT-based Smart Pole system for mitigating road accidents. The system integrates various sensor devices such as CCTV, air quality sensors, weather sensors, and warning speakers, all connected through a LAN network and supported by solar panels. The research findings show that the Smart Pole system can monitor air quality (PM2.5, PM10), weather conditions, and other traffic-related factors in real-time, enabling traffic managers to provide early warnings and rapid responses to potential hazards. With the application of Power over Ethernet (PoE) and solar panels, the system can operate efficiently without relying on external energy sources. The use of Face Analytics allows for the detection of risky behavior from drivers, while audio and visual warnings enhance driver awareness. The implementation of IoT-based Smart Pole technology can improve road safety by providing real-time data that is useful for traffic managers and road users, and it significantly contributes to the development of safer and more efficient smart city concepts.